Isolation and characterization of mammalian orthoreovirus type 3 from a fecal sample from a wild boar in Japan - Zhang, Wenjing; Kataoka, Michiyo; Doan, Yen Hai; Oi, Toru; Furuya, Tetsuya; Oba, Mami; Mizutani, Tetsuya; Oka, Tomoichiro; Li, Tian-Cheng; Nagai, Makoto (Archives of virology, 2021)
Mammalian orthoreoviruses (MRVs) have been identified in various mammalian species, including humans, bats, and pigs. However, isolation and complete genome sequences of MRVs from wild boars have not yet been reported. In this study, we isolated, sequenced, and analyzed an MRV from a free-living wild boar in Japan using the porcine-sapelovirus-resistant cell line N1380. Complete and empty virus particles were obtained from the N1380 cell culture supernatants, and complete genome sequences were obtained from complete virus particles. Sequence analysis revealed that the isolated MRV, named TY-14, could be classified as MRV3 and had a close genetic relationship to an MRV2 isolate from a lion in a Japanese zoo (L2, L3, and M3 genes) and a human MRV2 isolate from Japan (S2 gene). Phylogenetic analysis showed that TY-14 clustered only with bat MRVs in the M1 phylogenetic tree but formed a cluster with several animal MRVs in the M2 and S3 phylogenetic trees and branched independently in the L1, S1, and S4 phylogenetic trees, suggesting a genetic relationship to viruses of unknown origin. Recombination events were identified in the M2 gene. These results suggest that TY-14 was generated by reassortment and recombination events involving MRVs circulating in Japan, viruses from bats, and other viruses of unknown origin.